Design and development of enhanced anti surge control by using smith predictor method / Bassam Ahmed Mohammed Al-Khelly - Bassam Ahmed, Mohammed Al-Khelly (2017)
The importance of the anti surge control has became highly concern with the rapid increment of using compressors in industrial technology now a days. The applications of the compressors is varying depends on the process and the product ,this research has designed and developed anti surge controller for pneumatic compressors which are widely used in most of the industrial technologies to supply the plants with required compressed air for continues process and most of the process needs a compressed air with pressure of P = 7 bar, the flow is vary from compressor to others and from process to process this research has been concerned on the most used flow which is Q = 15.66 m3/min ,according to the process operation surge will occur when sudden blockage happened or during low demand so the process pressure will increase from 7 bar up to 9 bar before the compressor shutdown because of high vibration that yields from the high pressure most of the anti surge control are either PI or PID control and even that these controllers cannot predict the surge phenomena and the worst is the control valve is opened by 10% to 25% so these controllers has been designed and developed by using Smith predictor method and this enhanced Anti Surge controller has been demonstrated by using MATLAB/Simulink the enhanced Anti surge controller prove of an enhancement faster than normal PI or PID controller the result of the enhanced Anti surge controller reach up to 50% of time needed by the normal PI or PID controller Keywords: anti surge control, smith predictor method iv